Dampak Kemiringan Lahan terhadap Kadar Hara dan Produksi Kelapa Sawit - Desrihastuti, Desrihastuti; Maryanti, Adelina; Sabli, T. Edy; Mahendra, Ilham Aghi; Hardi, Noer Arif (Politeknik Negeri Lampung, 2024)
Palm oil is one of Indonesia's sources of foreign exchange, derived from government, private, and smallholder plantations. However, palm oil production from smallholder plantations is relatively poor due to low-quality seeds, non-standard technical culture, low soil fertility, and a lack of attention to the topography and slope of the ground during planting. Therefore, this research aims to characterize the growth and production of oil palm based on soil and plant nutrient content on various land slopes. The research was conducted on an oil palm plantation in Baru Village, Siak Hulu District, Kampar Regency, Riau Province, Indonesia. Oil palm plants have been in production for seven years. The methods used in this research are survey methods, observation, and laboratory analysis. The research design used a non-factorial randomized block design. The research factor is the land slope, with three treatment levels consisting of flat land (0–8%), land slope 8–18%, and land slope 18–28%. The parameters observed in this research include land topographic characteristics, physical and chemical properties of soil, plant nutrient content, and agronomic characteristics of oil palm plants. The observation results showed that trunk circumference, number of fruit bunches per tree, and weight of bunches per tree gave better results on a slope of 8–18%. This is due to soil conservation measures in the form of rather deep depressions around the plant plates. However, the P and K nutrient levels of oil palm plants in this research area are included in the deficiency category. As a result, this research can help make decisions about fertilizer management and land usage in oil palm plantation areas with sloping topography.